Study of Hardened Properties of Rubcrete Incorporated with SCMs (SF, FA, RHA): A Sustainable Approach (International Journal of Innovative Research in Computer Science & Technology, 2022)
This research focuses on the production of  concrete with possible use of agricultural and industrial  wastes in combined form as replacement to OPC along with  use of waste rubber tire granules as coarse aggregate. The  primary objective of this research is to is to check possible  use of ternary blend rubcrete in non- structural uses like  pavements. In this research the optimum proportion of combined  ternary mix (FA, SF, RHA) as partial replacement of  binder/cement in natural aggregate concrete of M35 grade  among the selected proportions were evaluated at the end of  7 and 28 days. Among the various proportions, the optimum  combined proportion was found to be 40% replacement  (10%SF, 10%RHA & 20%FA). The natural coarse  aggregates (NA) of the optimum ternary blend were further  replaced with waste tire granules (in proportions of 20%,  30% and 40%) and examined at end of 7 and 28 days. The  optimum proportion of rubber (RA) in ternary blend  rubcrete was found to be 20% as values above this  percentage showed tremendous decrease in strength.  Detailed experimental study of the fresh concrete property  (workability) was performed & the compressive strength,  flexural strength tests were carried out at the end of 7 and  28 days. Also, water absorption and loss in weight due to  acid attack was examined at the end of 28 days. It is  followed by SEM analysis and XRD analysis of the  optimum proportions in comparison to control mix which  justifies the results of this research. This research paves the  way towards sustainable, cost efficient and environment  friendly construction.
Keywords: SCM- Supplementary Cementitious Materials; SF- Silica Fume; FA-Fly Ash; RHA- Rice Husk Ash; OPC- Ordinary Portland Cement NA- Natural Aggregate; RA- Rubber Aggregate CSH- Calcium Silicate Hydrate; CH- Calcium Hydroxide; SEM- Scanning Electron Microscopy; XRD- X- Ray Diffractio